High power laser diodes/superluminescent diodes - Han, IK (KOREAN PHYSICAL SOC, 2004)
The author's group has developed multiple quantum well (MQW)-based diffraction-limited high power laser diodes and superluminescent diodes (SLDs). For example, 1.55-mum InGaAsP tapered lasers with a maximum power of CW 2.45 W and a diffraction-limited power of CW 1 W have been reported. The author and co-authors have also developed 1.55-mum InGaAsP SLDs with an optical power of 20 mW and simultaneously 3dB bandwidth of 130 nm. The author presents recent results on the quantum dot (QD) structures and explains potential possibility of QD-based devices to prevail over the performances of MQW-based devices in terms of diffraction-limited high power laser diodes and SLDs.
Keywords: LINEWIDTH ENHANCEMENT FACTOR; LIGHT-CURRENT CHARACTERISTICS; QUANTUM-WELL LASERS; SUPERLUMINESCENT DIODE; DOT LASER; PERFORMANCE; FILAMENTATION; OPERATION; GAIN